ANALISIS PROFITABILITAS DAN EFISIENSI BUDIDAYA KOPI DI PTP NUSANTARA IX (PERSERO) KEBUN GETAS SALATIGA - Endang Siti Rahayu (University of Jember, 2012)
This study was aimed to determine the amount of revenue and profit of coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation, to identify the profitability of coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation, and to determine the efficiency of coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation. The basic method used in this study was descriptive, analytical method. The research location was determined purposively. The type of data in this study was secondary data. Methods of data analysis used were analyses of total cost, revenue, profit, profitability and efficiency of coffee cultivation. The results of analysis showed that the average total cost of coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation was IDR 5.879.062.630,00. The average of revenue obtained was IDR 5.879.076.254,00, so that the average of profit obtained by PTP Nusantara IX (Persero) Getas Salatiga Plantation was IDR 13.624,00. Profitability of coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation was IDR 54.495,00 which means that the coffee cultivation was profitable. Coffee cultivation at PTP Nusantara IX (Persero) Getas Salatiga Plantation has more than efficiency value more than one, that is, 1,000002. This means that each IDR 1.00 cost spent in the initial cultivation will provide revenue by 1,000002 times of the cost spent. Keywords: Coffee, Profitability, Efficiency